Ruthenium(II) Polypyridyl Complexes and Their Use as Probes and Photoreactive Agents for G-quadruplexes Labelling - Julie Jiang; Titouan Teunens; Jérôme Tisaun; Laura Denuit; Cécile Moucheron (Molecules, 2022)
Due to their optical and electrochemical properties, ruthenium(II) polypyridyl complexes have been used in a wide array of applications. Since the discovery of the light-switch ON effect of [Ru(bpy)2dppz]2+ when interacting with DNA, the design of new Ru(II) complexes as light-up probes for specific regions of DNA has been intensively explored. Amongst them, G-quadruplexes (G4s) are of particular interest. These structures formed by guanine-rich parts of DNA and RNA may be associated with a wide range of biological events. However, locating them and understanding their implications in biological pathways has proven challenging. Elegant approaches to tackle this challenge relies on the use of photoprobes capable of marking, reversibly or irreversibly, these G4s. Indeed, Ru(II) complexes containing ancillary π-deficient TAP ligands can create a covalently linked adduct with G4s after a photoinduced electron transfer from a guanine residue to the excited complex. Through careful design of the ligands, high selectivity of interaction with G4 structures can be achieved. This allows the creation of specific Ru(II) light-up probes and photoreactive agents for G4 labelling, which is at the core of this review composed of an introduction dedicated to a brief description of G-quadruplex structures and two main sections. The first one will provide a general picture of ligands and metal complexes interacting with G4s. The second one will focus on an exhaustive and comprehensive overview of the interactions and (photo)reactions of Ru(II) complexes with G4s.